Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan Dengan Self-Efficacy Sebagai Variabel Mediasi - Malika Izdihar Azzahro; Damajanti Sri Lestari; Anita Asnawi; Priyanto Priyanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Human resources (HR) are an important asset that determines the success or failure of an organization. The importance of integrating training, motivation, and self-efficacy into HR management and development strategies that are not only oriented towards improving competence but also strengthening psychological aspects that support sustainable performance. This study uses a quantitative approach with an associative research type that aims to analyze the effect of training and work motivation on employee performance with self-efficacy as a mediating variable. This approach was chosen because it is able to explain the causal relationship between variables and test the mediating role in the research model. Overall, the results of the study confirm that employee performance in this context is more influenced by internal psychological factors, namely motivation and self-efficacy, than by external interventions such as training. These findings have practical implications for organizations that improving performance requires not only training programs but also strategies to strengthen motivation and build self-confidence through positive feedback, challenging assignments, and a supportive work environment. Based on the results of the study conducted on the influence of training and work motivation on employee performance with self-efficacy as a mediating variable, it can be concluded that training and work motivation have different effects on improving the performance of white-collar employees in Surabaya. Thus, this study confirms that improving employee performance is more effectively achieved through strengthening work motivation and increasing self-efficacy than by relying solely on formal training.